Mucormycosis in pre‐COVID‐19 and COVID‐19 era: A study of prevalence, risk factors and clinical features. Issue 5 (7th September 2022) - Arjmand, Parisa; Bahrami, Milad; Mohammadie, Zahra Eslami; Taherynejad, Mohammadhossein; Khorasani, Negar Yeganeh; Mehrad‐Majd, Hassan; Roshanzamir, Imaneh; Bakhshaee, Mehdi
Abstract: Objective: Mucormycosis is a rare yet devastating fungal disease with a frequently fatal outcome. The purpose of this study was to compare the prevalence of mucormycosis, evaluate its risk factors, and assess the patients' outcomes in pre‐COVID‐19 and COVID‐19 era. Methods: In this retrospective observational study, clinical data of 158 patients with confirmed histopathological diagnosis of mucormycosis were collected from the medical records departments of Imam Reza and Ghaem hospitals, Mashhad, Iran during 2018–2021. The collected data were risk factors associated with mucormycosis including age, gender, underlying diseases, details of corticosteroid administration, and complications such as blindness and mortality. Results: Of 158 studied patients, 48 patients were diagnosed in the pre‐pandemic period whereas 110 cases were admitted during the pandemic era. COVID‐19 associated mucormycosis (CAM) was observed in 58.1% of the pandemic cases. In the pre‐pandemic period, cancer (89.5% vs. 39%, p < .001) was significantly more prevalent while during the pandemic era, the prevalence of diabetes mellitus (16.7% vs. 51%, p < .001) was remarkably higher. Moreover, the mortality rate of mucormycosis was considerably reduced after the pandemic (64.6%–45.4%), especially in CAM patients (35.9%). Conclusion: The COVID‐19 pandemic has led to an increased prevalence of mucormycosis, due to the convergence of interlinked risk factors such as diabetes mellitus, corticosteroid therapy, and COVID‐19. Therefore, clinicians must be aware of the probable occurrence of mucormycosis in the first or second week of COVID‐19 infection in vulnerable patients and use the steroids cautiously. Level of evidence: 4 Laryngoscope Investigative Otolaryngology, 2022. Abstract : Mucormycosis (MM), also known as black fungus, is a lethal opportunistic disease with a yearly incidence of 1.7 cases per one million population. In hospital records, there is compelling evidence that the prevalence of mucormycosis has increased during the COVID‐19 pandemic. The current study was conducted to compare the prevalence of mucormycosis, evaluate its risk factors and assess the patients' outcomes in pre‐COVID‐19 and COVID‐19 era.